Identification of Dermatophyte Causes Tinea Capitis in Users of Hair Oil Made From WAX in Manggala District, Makassar - Awaluddin; Waji, Resi Agestia; Debit, Yohanis (Jurnal Kedokteran Universitas Palangka Raya, 2022)
Tinea capitis is a fungal infection on the skin and scalp caused by dermatophytes. Using Excessive of wax-based hair oil can trigger dandruff, where research aimed to identify the type of dermatophyte fungus that caused Tinea capitis on the scalp of users of hair oil made from wax. This type of research used descriptive research with laboratory observation methods. The subjects of this research were users of hair oil made from wax in the district of Manggala, Makassar, which amounted to 10 people. Data collection techniques in this research were observation and giving questionnaires to respondents and presented descriptively in the form of pictures and tables and explained in narrative form. The results showed that of the 10 samples examined, 8 samples were identified that contained dermatophyte fungi, namely Trichophyton rubrum and Trichophyton tonsurans species and were 2 samples identified as non-dermatophyte fungi, namely Candida albicans and Aspergillus niger species. Based on the results of the research that has been carried out, it can be concluded that the types of  dermatophyte fungi present in users of hair oil made from wax are Trichophyton rubrum and Trichophyton tonsurans and there are2 samples identified by non-dermatophyte fungi, namely Candida albicans and Aspergillus niger species. Based on the results of the research that has been done, it can be concluded that the types of dermatophyte fungi found in users of hair oil made from wax are Trichophyton rubrum and Trichophyton tonsurans.